The phenomenon of drugs in Iraq and its impact on the Iraqi national security - Kamel Kazem, Lecturer, Dr. Dhifaf (The college of law and political science journal, 2023)
The paper provides an overview of the phenomenon of drug abuse in Iraq,ZKLFKVSUHDGUHPDUNDEO\LQ,UDTDIWHUWKH86RFFXSDWLRQRIWKHFRXQWU\LQ2003 andLQFUHDVHGZLWKWKHHQWU\RIWKHWHUURULVWRUJDQL]DWLRQ,6,6LQ2014, and the reasonsthat led to its spread and ways of entering the country as the geographical locationof Iraq between producing and consuming countries and its source contributed toThe ease of its entry into it, until Iraq turned from a consumer country to a producerand a passage for it to the rest of the other countries, and the accompanyingviolence, political and security instability, poor economic conditions and the lackof border control, all of which contributed to the increase of the problem more thanothers, which generated political, economic and social dimensions that affected Onthe national security of the country, the efforts of the Iraqi and international Ministryof Health are still weak to confront and combat the phenomenon.